Epifani Wajah Liyan dalam Kekerasan Seksual Terhadap Perempuan (Telaah Menurut Konsep Wajah Emmanuel Levinas): The Epiphany of the Face of the Other in Sexual Violence Against Women (Study According to Emmanuel Levinas's Concept of the Face) - Enggo, Edelbertus Edwardo; Firmanto, Antonius Denny (Undiksha, 2024)
This study aims to delve into and explore the meaning of the epiphany of the other's face in the context of sexual violence against women, utilizing Emmanuel Levinas' philosophy as the primary theoretical foundation. The research will investigate how Levinas' concept of the epiphany of the face can offer new insights and provide a profound understanding of the phenomenon of sexual violence against women. Employing a Literature Review method with a qualitative approach, this study aims to examine Levinas' concept of the face and apply it to the reality of sexual violence against women. Levinas underscores the importance of ethics as the basis for human relationships, particularly through the concept of the face as the gateway to understanding the uniqueness and dignity of each individual. Building on this issue, the author finds that the epiphany of the other's face can provide deeper insights into the uniqueness of women who are victims of sexual violence, emphasizing the ethical responsibility to actively engage in protecting and defending victims of sexual violence. Furthermore, the significance of subjective involvement and responsibility highlights the need for personal engagement in humanitarian relationships. The phenomenon of sexual violence against women paints a troubling picture of the existence of a woman's face. The presence of the other's face (women) that should be considered as the encounter between the